Use of Digital Media Platforms for Social Change in Nigeria - Joy Collins-Dike; Richard N. Amadi; Dike Harcourt Whyte; Njoku C. Justice; Hauwa Mohammed Kawo (Budapest International Research and Critics University, 2025)
The increasing penetration of digital media platforms in Nigeria has significantly transformed social activism, civic engagement, and public discourse. This study examines the role of digital media in driving social change, focusing on its impact on advocacy, governance, human rights, and community mobilization. Platforms such as Twitter, Facebook, WhatsApp, and Instagram have become critical tools for raising awareness, shaping public opinion, and influencing policy decisions. The #EndSARS movement, among other online campaigns, has demonstrated how digital activism can translate into real-world change. Additionally, digital platforms have facilitated access to educational resources, health information, and grassroots fundraising initiatives, bridging gaps in communication and social development. However, challenges such as digital illiteracy, misinformation, internet censorship, and disparities in digital access continue to hinder the effectiveness of digital advocacy in Nigeria. Despite these obstacles, the study highlights the growing potential of digital media as a force for social transformation and calls for improved digital literacy, policy reforms, and enhanced infrastructure to maximize its impact. The findings contribute to understanding how digital media can be leveraged for inclusive and sustainable social change in Nigeria. In the area of education and health, digital platforms have played a transformative role. Online learning platforms and social media pages provide access to educational resources, bridging the gap for people in underserved communities.